Factors Influencing Participation Of Producers In Farmers’ Market – An Analysis Of Siddipet Rythu Bazaar (Telangana) - Shalendra,; Sangamesh Angadi,; Madhulatha C, (Journal of Agricultural Extension Management, 2026)
Developing local food system by providing market access to farmers close to the production area has the potential to overcome various challenges faced by farmers in effective marketing of their produce mainly smallholder cultivating perishables. The Government has recognised the potential of local element in agriculture as suggested by the introduction of various reforms including farmers’ market. The concept has been experimented in various states with different names like Rythu Bazaars in Telangana. The concept has so many dimensions to be analysed to understand its effective implementation. However, an attempt has been made in the present paper to understand the factors influencing the participation of producers in farmers’ market by taking a case of Siddipet Rythu Bazaar. The analysis is based on the results of Probit Regression Model run on the primary information collected from 200 sample farmers. The analysis reveals that variables like gender, family size, production of vegetable and availability of transport facility have significant and positive influence on the participation of farmers in Rythu Bazaar. However, factors like market orientation and age had significant but negative influence suggesting that youth with better market orientation tends to explore market opportunities outside such models. Rythu Bazaars have the potential to serve as an effective market access tools for smallholders mainly cultivating perishables and acquiring certain characteristics in terms of family size and presence of women to contribute. Though, youth are observed to be inclined to participate in models other than Rythu Bazaars.